I. S. A. Baud. Forms of Production and Women's Labour: Gender Aspects of Industrialisation in India and Mexico. New Delhi: Sage Publications. 1992. 321 pp.Hardbound. Price: Indian Rs 295.00. (The Pakistan Development Review, 1993)
The literature on female labour in Third World countries has become quite extensive. India, being comparatively more advanced industrially, and in view of its size and population, presents a pictures of multiplicity of problems which face the female labour market. However, the author has also included Mexico in this analytical study. It is interesting to see the characteristics of developing industrialisation in two different societies: the Indian society, which is conservative, and the Mexican society, which is progressive. In the first chapter of the book, the author explains that he is not concerned with the process of industrialisation and female labour employed at different levels of work, but that he is interested in forms of production and women's employment in large-scale production, petty commodity production, marginal small production, and self-employment in the informal sector. It is only by analysis of these forms that the picture of females having a lower status is understood in its social and political setting.